Revisiting Postmodernism - Farrell, Terry; Furman, Adam Nathaniel (RIBA Publishing, 2017)
Revisiting Postmodernism' offers an engaging, wide-ranging and highly illustrated account of postmodernism in architecture from its roots in the 1940s to its ongoing relevance today. This book invites readers to see Postmodernism in a new light: not just a style but a cultural phenomenon that embraces all areas of life and thrives on complexity and pluralism, in contrast to the strait-laced, single-style, top-down inclination of its predecessor, Modernism. While focusing on architecture, this book also explores aspects such as urban master planning, furniture design, art and literature. Looking at Postmodernism through the lens of examples from around the world, each chapter explores the movement in the UK on the one hand, and its international counterparts on the other, reflecting on the historical movement but also how postmodernism influences practices today. This book offers the insider's view on postmodernism by Sir Terry Farrell, a recognised pioneer in the field of postmodern architecture and a prestigious and authoritative participant in the postmodern movement. Written by one of postmodernism's greatest pioneers Traces the origins of Postmodernism back to earlier than is generally suggested, and posits that figures usually considered as pure Modernists in fact sowed the seeds of Postmodernism - redefining our notion of what the term means. Covers postmodernism as it exists today and looks at examples from current postmodern practices. Focuses on architecture but also embraces other areas of design, culture and life, including urban planning and place making. Engaging, accessible tone, suitable for a broad range of readers - architects, students, designers and the public.